Trunk muscle composition 2 months after hip fracture: Findings from the Baltimore Hip Studies - Hicks, Gregory E. (Arch Phys Med Rehabil, 2018)
OBJECTIVE: To determine if hip fracture patients would have smaller cross-sectional area (CSA) and lower radiological attenuation (suggesting greater fat infiltration) in all trunk muscles as compared to healthy older adults. DESIGN: Cross-sectional analysis of computed tomography scans. SETTING: Clinical imaging facility. PARTICIPANTS: Forty-one white participants (19 men, 22 women) from the Baltimore Hip Studies 7(th) cohort (BHS-7) at 2-months post-fracture were compared to 693 white participants (424 men, 269 women) from the Health, Aging and Body Composition Study (Health ABC) at the year 6 visit. INTERVENTION: Not applicable. MAIN OUTCOME MEASURES: Trunk muscle CSA and attenuation values were obtained from a single 10 mm, axial computed tomography (CT) scan completed at the L4-L5 disc space in each participant. RESULTS: The hip fracture cohort had significantly smaller CSA for all trunk muscles (range: 12.1 to 38 % smaller) compared to the Health ABC cohort (p<.01), with the exception of the rectus abdominus muscle in men (p=.12). But, hip fracture patients, particularly female patients, had higher attenuation levels (lower intramuscular fat) in all trunk muscles (p<.0001). CONCLUSIONS: Findings are consistent with atrophy of the trunk muscles in the hip fracture population without a high level of intramuscular fat. Future work should evaluate the role of trunk muscle composition in the functional recovery of older adults following hip fracture.